The Therapeutic Potential of Topically Applied Essential Oils in Preventing or Treating Early Borrelia burgdorferi Infection: A Review - Dolan, Keren; Courie, John; Tims, Michael (Planta Medica, 2025)
Lyme disease, caused by Borrelia burgdorferi, presents significant diagnostic challenges, often leading to delayed treatment and decreased therapeutic response to conventional antibiotics. This review aims to evaluate the potential of plant essential oils, known for their bacteriostatic, bactericidal, and anti-quorum sensing properties, as prophylactic, adjunct, or complementary treatments during the early stages of B. burgdorferi infection. The authors explore how these essential oils can target adaptive mechanisms and interactions of B. burgdorferi, including complement regulator-acquiring surface proteins (CRASPs), immune modulation, motility, chemotaxis, biofilm formation, efflux-pump mechanisms, and cyst formation. The authors identify current research gaps and propose frameworks to substantiate the clinical efficacy of essential oils for Lyme disease treatment. This review indicates that essential oils have multifaceted therapeutic potential and could provide a viable option for early intervention in Lyme disease. Further research is necessary to confirm their clinical applicability and safety.
Keywords: Lyme disease; Lyme borreliosis; Borrelia burgdorferi; essential oils; volatile oils